Cowpea Yield as Affected By Level and Time of Mineral Phosphorus Fertilizer Application in the Guinea Savanna Agro-Ecological Zone of Ghana (Global Journal of Science Frontier Research, 2014)
Phosphorus, although not required in large quantities, is very critical to cowpea production because of its multiple effects on nutrition; shoot development and its influence on nodulation. Phosphorus application stimulates plant root growth, early flowering, enhances fruiting, initiate nodule formation as well as increase in yield of cowpea. In spite of this immense importance of P in soils, its availability to cowpea growth and development is influenced by several factors, which include level and time of application. Knowledge in level of P and time of application to facilitate timely availability of the P fertilizer to improve cowpea yield is critical in order to avertthe continues reduction of cowpea yield by farmers. As a result a 3×4 factorial experiment arranged in split-plot design was conducted at the University for Development Studies experimental site, Nyankpala near Tamale in the northern region of Ghana campus to determine the appropriate P fertilizer levels and timing of application. Three levels of P fertilizer; 24, 48 and 60 kg ha -1 P was applied at 30, 15 days before plating. However, a third application was implemented at sowing.
Keywords: phosphorus; nodule number; nodule weights; time of application